Vavilov–Cherenkov Radiation in an Inclined Dielectric Plate and Violation of Azimuthal Symmetry; Physics of Particles and Nuclei Letters; Vol. 16, iss. 2 - Potylitsyn A. P. Alexander Petrovich (2019, 2019)
Title screen